Aerodynamics of high-bypass-ratio aeroengine nacelles: numerical and experimental investigation - Tejero, Fernando; MacManus, David G.; Sánchez-Moreno, Francisco; Schreiner, B. Deneys J.; Hill, Andrea; Sheaf, Christopher T.; Ramirez-Rubio, Santiago (American Institute of Aeronautics and Astronautics (AIAA), 2025)
This work presents a numerical and experimental investigation of the nacelle aerodynamics for high-bypass- ratio aeroengines. A conventional nacelle that is representative of a current standard, and a compact design that is envisaged for future aeroengines, were optimized with an existing computational method. Both nacelles were tested in a large-scale transonic wind tunnel. For the first time, the aerodynamic benefits of compact nacelles are demonstrated through an experimental test campaign. Measurements and computational fluid dynamics (CFD) simulations confirmed the drag reduction of compact configurations across a wide range of operating points with different flight Mach numbers, mass-flow capture ratios, and angles of attack. For midcruise conditions with a Mach number of 0.85, this was a drag reduction of 8.5% and 8.8% for the measurements and CFD, respectively. These benefits are similar to an isolated optimization, that is, not installed in the wind tunnel, which confirmed the capabilities of the method to identify the drag benefit of compact designs. Relative to the measurements, the main aerodynamic characteristics on the nacelles were captured by CFD in terms of isentropic Mach number distributions and shock location. This work provides a quantitative evaluation for the use of CFD within an industrial setting for nacelle design and analysis.
Keywords: Aerospace & Aeronautics; 40 Engineering